Recordkeeping in international organizations archives in transition in digital, networked environments - Boel, Jens; Sengsavang, Eng (Routledge, 2020)
Recordkeeping in International Organizations offers an important treatment of international organizations from a recordkeeping perspective, while also illustrating how recordkeeping can play a vital role in our efforts to improve global social conditions - Provided by publisher.